PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII1 SMPN 1 TELUK KUANTAN - Marni Swasti; Nahor Murani Hutapea; Sakur Sakur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is a class action research that aims to improve the learning process and to increase the outcomes of mathematics learning of the students by applying discovery learning. The subjects of this research are the students of classSMPN 1 Teluk Kuantan at the second semester of academic years 2017/2018 which total number of participants are 30 students, consists of 14 male students and 16 female students with heterogeneous academic achievements. This research has two cycles. Each of them has four stages: planning, implementation, observation, and reflection. The data collecting instruments consist observation sheet (learning process) and the students' worksheet. Learning device used in this research consists of Syllabus, Lesson plan, and Student work sheet. The data were analized by narrative descriptive and statistical descriptive. The data were obtained from the observation sheets of teacher and students activities that showed the learning process has improved after the model being implemented. From the data of the student’s evaluation test, it showed that that the frequency of the number of students who reached the standard category, good and very good in the frequency distribution table increased from base score to Quiz I, and from Quiz I to Quiz II. The number of students who reached the Minimum Mastery Criteria from the basic score to Quiz I increased by 3 people with a 10% increase, and from Quiz I to Quiz II increased by 4 people with an increase of 13.4%.Key Words : The outcomes of mathematics learning, Discovery Learning, class action research